Dietary Intake and Nutritional Knowledge: Study in Haemodialysis Patients with Hypertension and Diabetes Mellitus in RUSD Dr. Saiful Anwar Malang - Yade Kurnia Yasin; Defanda Tritya; Septian Riski Hidayah; Anggun Rindang Cempaka; Dewi Retno Sariwulan; Nurussyariah Hammado (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Hypertension and Diabetes Mellitus are the most common causes of Metabolic Syndrome, one of which leads to Chronic Kidney Disease (CKD). Risk factors associated with this condition are diet and nutritional knowledge. This study aims to determine differences in nutritional intake and nutritional knowledge in patients with kidney disease on hemodialysis who have comorbid hypertension and/or diabetes mellitus and/or both. The number of respondents in this cross-sectional study was 27 outpatients undergoing hemodialysis at RSUD Dr. Saiful Anwar Malang, taken by consecutive sampling which met the inclusion criteria. The variables studied were dietarily obtained from the SQ-FFQ and nutritional knowledge was obtained from interviews using a questionnaire form containing questions related to diet, food consumed, restricted foods, and foods to avoid. The results showed that 17 hemodialysis patients suffered from hypertension and 10 patients with hypertension and diabetes mellitus. There was no difference in dietary intake between the hypertension group and hypertension and the diabetes mellitus group (p>0.05), the results of the analysis of nutritional knowledge also showed no difference between the two groups (p>0.05). This study concluded that hemodialysis patients who experienced hypertension and hypertension with Diabetes Mellitus did not show differences in dietary intake and nutritional knowledge.